Supabox / Amirul Asyraf Fauzi ... [et al.] - Fauzi, Amirul Asyraf; Mohd Rasidi, Siti Nur Syazwani; Wan Nawi, Wan Annisa Sofea; Musa, Ahlam Sakinah; Ahmad Sanusi, Nurina Nayli; Mazlan, Midhati Auni; Sukri, Nurhafizati (2022)
Supabox is a 3 in 1 cooler with a compressor designed to be lightweight and portable, given its purpose of cooling and storing items to preserve their temperature for outdoor activities. Supabox comes with two products, the main product is a cooler with a compressor that can hold food or drinks at various temperatures that the consumer can control and powered by a large capacity portable battery that can be charged or replaced at any time. Next is our add-on product which is a storage cooler without compressors that can provide extra freezer space for the consumers. Both product’s uniqueness is it has a portable table, a portable chair, and the add-on product can be connected to the main product by a connector made by magnet and transferable hole to share the cooling air. Supabox is marketable for a wide range of potential customers whether for personal use, outdoor or indoor use. Since our product is portable, chargeable and lightweight our major target customer was from metropolitan areas such as office workers, students and ramblers. As among Malaysian activities like trips, travel and picnics trending after lockdown orders were uplifted by the government especially Negeri Sembilan peoples. Due to its versatility to fit nearly anywhere and be more efficient than existing cooler boxes, it will also become a convenient approach in Malaysia or western countries. We also target online customers across Malaysia and wholesale through a manufacturer's agent, so it is easily accessible and responsive to increase our market. Our Supabox is unique and a brand-new innovation in the market thus our product is expected to create a positive competitive advantage in the storage and cooler product for outdoor activities and minimalism. After 3 years of introducing our Supabox into the market, we estimated the demand for Supabox will rise and have a high potential to be profitable due to its innovation of its usefulness, technology and simplicity.